Exploring Students’ Academic Procrastination at Indonesian Senior High School in Indonesia - Siti Faradilla; Safrul Muluk; Rahmi Rahmi; Fatayatul Hahani (Journal of Innovation in English Education and Language Teaching, 2024)
Academic procrastination has been considered one of the most prevalent issues hampering students’ academic achievement. It is the intentional postponement of academics and activities, despite the procrastinator’s awareness that this is detrimental to the learning process. To delve into this particular issue, the researchers examined the causes of academic procrastination and the strategies provided by teachers to deal with students’ academic procrastination. A qualitative approach was utilized to investigate the issue by using an interview data collection technique. The investigation was conducted at Senior High School 7 Banda Aceh, Indonesia. Three teachers and 5 students were involved in this qualitative research. Findings indicated that two factors caused students’ procrastination, internal and external factors, are poor time management, students’ health condition, social media addiction, and task aversiveness. Teachers implement several strategies to deal with these conditions, including giving motivation, setting up a better schedule or time management, and collaboration between teachers and parents